2020
DOI: 10.1021/acs.energyfuels.0c01932
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Primary Moisture on Methane Adsorption within Lower Silurian Longmaxi Shales in the Sichuan Basin, China

Abstract: Moisture significantly affects the adsorption capability of gas shales for methane (CH4), the main component of shale gas. Primary moisture, i.e., the moisture that exists in in situ shale reservoirs, is therefore crucial to estimate and produce shale gas resource. Aiming to understand the influences of primary moisture on CH4 adsorption on shale samples, the occurrence of primary moisture in shales gathered from the Lower Silurian Longmaxi Formation located in southern Sichuan Basin of China was experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 73 publications
2
34
0
Order By: Relevance
“…In general, the scCO 2 –H 2 O exposure alters the CO 2 adsorption capability of all of the coals. To further investigate the effect of scCO 2 –H 2 O on the CO 2 adsorption capability of coals and to better explore the equilibrium adsorption behavior, in this study, we applied the Ono–Kondo lattice model provided with high predictivity for reservoir fluid adsorption equilibrium. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the scCO 2 –H 2 O exposure alters the CO 2 adsorption capability of all of the coals. To further investigate the effect of scCO 2 –H 2 O on the CO 2 adsorption capability of coals and to better explore the equilibrium adsorption behavior, in this study, we applied the Ono–Kondo lattice model provided with high predictivity for reservoir fluid adsorption equilibrium. , …”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the effect of scCO 2 −H 2 O on the CO 2 adsorption capability of coals and to better explore the equilibrium adsorption behavior, in this study, we applied the Ono− Kondo lattice model provided with high predictivity for reservoir fluid adsorption equilibrium. 19,77 The simplified Ono−Kondo equation is 78 Energy & Fuels 12 and Table 6, respectively. The modeling curves agree well with the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Figure a, microwave irradiation promotes rapid increase in temperature of the shale matrix, therefore significantly promoting physically adsorbed CH 4 desorption from shale. , Furthermore, microwave irradiation decreases adsorption pores for accommodating CH 4 of the dry shale matrix with a diameter below 10 nm, while it increases meso- and macropores with a diameter greater than 10 nm (Figure b) . Such transformation in full-scale pores of a dry shale matrix can not only promote CH 4 desorption but also strengthen diffusion capability of previously desorbed CH 4 within gas-bearing shale reservoirs. , In addition, the shale matrix contains a wide variety of inorganic minerals mainly including nonclay minerals, such as quartz, pyrite, calcite, feldspar, dolomite, and plagioclase, and clay minerals, such as illite and smectite. , The dielectric properties of typical inorganic materials of shale are listed in Table . , As shown in eq , the dielectric constant is measured by the real part of relative permittivity, indicating how much energy can be stored in the material, and by the loss factor, that is, the imaginary part of the relative permittivity, indicating the ability of converting the stored energy into heat. Among these minerals, pyrite, illite, and smectite with a greater dielectric constant and loss factor always show better microwave heating performance .…”
Section: Introductionmentioning
confidence: 98%
“…It is worth noting that the actual gas-bearing shale reservoir contains primary moisture. , Numerous studies have confirmed that H 2 O shows remarkable impact on CH 4 adsorption, desorption, and migration within the reservoir. Given the strong electric dipole and high polarity of the H 2 O molecule, the adsorption strength of H 2 O on shale is higher than that of CH 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation